The Limits of Transformation: Contemporary Applications of Karl Polanyi - England, Christopher (Journal of Australian Political Economy. Summer2015/16, Issue 76, 2015)
The article explores the conception of the Great Transformation (GT) by economic historian Karl Polanyi and its contemporary applications. Topics covered include the continued existence of free market fundamentalism as a prominent ideology and as a living political project, the persistence of free market utopianism, and Polanyi's genealogy of the market system. Also discussed are his conception of industrialism and his use of functionalist theory to build a unified image of the social system.
Political Science
Keywords: economics; free enterprise; functionalism; industrialism; political economy; social systems; utopias

Karl Polanyi's Genealogy of Utopian Liberalism - England, Christopher (Theory & Event, 2018)
Despite its centrality to current debates about globalization and neoliberalism, aspects of Karl Polanyi's The Great Transformation remain poorly understood. This article places Polanyi in conversation with Weber, Nietzsche, and Foucault in order to explicate his genealogy of utopian liberalism. This mode of thought emerged in the late 18[sup th] century as a response to the mass pauperism of the Industrial Revolution in England. It substituted a mechanistic naturalism for the political and ethical concerns of earlier economists. Polanyi shows that the allure of utopian liberalism is sustained because it functions as the public theodicy of a market society.
Political Science
Keywords: FOUCAULT; Michel; 1926-1984; NIETZSCHE; Friedrich; POLANYI; Karl; 1886-1964; genealogy; globalization; liberalism; neoliberalism; utopian liberalism

Karl Polanyi and the Rise of Fascism - England, Christopher M. (New Political Science, 2022)
This article reconstructs Karl Polanyi’s account of fascism’s rise in his 1935 article, “The Essence of Fascism.” Following the elevation of Hitler to power in 1933, Polanyi embarked on a reassessment of Nietzsche, Othmar Spann, Spengler, Evola, and other figures of the interwar conservative revolution. He argues that the fascist quest for national unity emerges when 19th century liberalism fails to address the growing atomization and economic dislocation of modern society. On the one hand, fascism valorizes the mythopoetic, prehistorical vitalism that liberal rationalism and social democracy sought to purge from public life. On the other, fascism aspires to a higher form of elitist, technological mastery than egalitarian states can achieve. These tensions, he predicts, will result in the radicalization and collapse of fascist regimes in a European war. This article illuminates Polanyi’s deep understanding of political modernity and the contemporary implications of his philosophical critique of the far right.
Political Science
Keywords: Karl Polanyi; conservative revolution; fascism; modernity; radical right